2022
DOI: 10.3390/medicina58030400
|View full text |Cite
|
Sign up to set email alerts
|

Review of History of Basic Principles of Burn Wound Management

Abstract: Thermal energy is an essential and useful resource to humans in modern society. However, a consequence of using heat carelessly is burns. Burn injuries have various causes, such as exposure to flame, radiation, electrical, and chemical sources. In this study, we reviewed the history of burn wound care while focusing on the basic principles of burn management. Through this review, we highlight the need for careful monitoring and customization when treating burn victims at each step of wound care, as their indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 141 publications
(145 reference statements)
1
4
0
3
Order By: Relevance
“…The pediatric burns were mainly shallow ° to deep ° combined deep burns in small and medium-sized areas. In most cases, wound healing or improvement could be achieved by regular dressing changes or covering with acellular dermis, which is basically consistent with previous studies [14,15]. This study showed that the early application of acellular dermis to cover the wounds of children with II° burns can shorten the healing time of the wounds compared with routine dressing changes.…”
Section: Discussionsupporting
confidence: 89%
“…The pediatric burns were mainly shallow ° to deep ° combined deep burns in small and medium-sized areas. In most cases, wound healing or improvement could be achieved by regular dressing changes or covering with acellular dermis, which is basically consistent with previous studies [14,15]. This study showed that the early application of acellular dermis to cover the wounds of children with II° burns can shorten the healing time of the wounds compared with routine dressing changes.…”
Section: Discussionsupporting
confidence: 89%
“…The stasis zone itself can have the chance to improve or even become necrotic in the first few days if the vascular perfusion is poor, resulting in more necrotic tissue, hence a wider and deeper burn area than before. 14 These patients are going through microvascular disorders, significant inflammatory responses and cardiovascular disorders which caused perfusion to become increasingly impaired. This not only causes worsening of the burn area which makes larger necrotic tissues, but also worsen the patient's overall condition systemically.…”
Section: Discussionmentioning
confidence: 99%
“…This not only causes worsening of the burn area which makes larger necrotic tissues, but also worsen the patient's overall condition systemically. 14 Inflammation from extensive tissue damage can also be a challenge considering the risk of systemic inflammatory response syndrome (SIRS) and multiple organ failure. [15][16][17][18][19][20] Meanwhile, the inflammatory response also have important role in the healing process, triggering a cascade of cytokines and growth factors that protect against the risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…A pressão arterial, a frequência cardíaca e a avaliação clínica da cor da pele não queimada são parâmetros utilizados para avaliar o estado circulatório. Devido ao aumento da resposta das catecolaminas após uma lesão térmica, 100-120 batimentos cardíacos por minuto são considerados dentro dos limites normais (AHUJA et al, 2016;SASAKI et al, 2022;KIM et al, 2022).…”
Section: Discussão Estabilização E Avaliação Inicialunclassified